KOMUNIKASI RITUAL NGALAP BERKAH PESUGIHAN DALAM PANDANGAN AGAMA BUDDHA (STUDI KASUS DI GUNUNG KEMUKUS KABUPATEN SRAGEN JAWA TENGAH) - Marjianto (Jurnal Pendidikan, Sains Sosial, dan Agama, 2018)
Communication Ritual Ngalap Berkah Pesugihan on the Perspective of Buddhism. (A case study at Gunung Kemukus Sragen Regency, Central Java). Research. State Buddhist College of Raden Wijaya Wonogiri Central Java. This reserach aims to explain the functions of communication ritual ngalap berkah pesugihan, to know the origin of Prince Samudra’s graveyard became a place of ngalap berkah pesugihan ritual, to know the procedures of ngalap berkah pesugihan ritual, to describe ngalap berkah pesugihan ritual in Gunung Kemukus on the perspective of Buddhism. This research uses qualitative approach. Through qualitative approach will be obtained data completely, certainly, so that it has high credibility. Case study is a strategy which is plenty used in qualitative research, the focus of a case study is stick on the paradigm that is naturalistic, holistic, culturalistic, and phenomenology. The researcher tries to describe the communication ritual of ngalap berkah pesugihan in Gunung Kemukus and to analyze through Buddhism perspective. The Phenomenon of ngalap berkah pesugihan in Gunung Kemukus with sex ritual on pon Thursday night or Kliwon Thursday night is clearly contradict with Buddhism’s teaching that is about morality on the five Buddhist precepts to three. There are four ways to achieve the prosperity; 1) Perfection in the initiative, diligent and eager to work, 2) perfection in the protection, keep the wealth acquired, 3) good friendship, make friend with the wise, 4) balance in life, do not waste the money but do not miserly as well. In addition to increasing worldly wealth source is: do not play a woman, do not get drunk, do not gamble and do not have a friendship that is not good.